Research of Kinematics and Workspace of 2-SPR/(U+UPR)P(vA) Reconfigurable Parallel Mechanism - Chunsheng Ma; Wenbo Mi; Xiaoqin Yin; Zhendong Ma (Jixie chuandong)
A 2-SPR/(U+UPR)P(vA) redundant parallel mechanism with reconfigurable kinematic pairs is proposed，which can be applied to parallel operation platform. Firstly，the spiral matrix of the 2-SPR/(U+UPR)P(vA) parallel mechanism is established，the DOF of the mechanism under the R and U phases are solved，and the DOF of the mechanism are verified by using modified Kutzbach-Grübler formula. Secondly，the closed-loop vector method is used to solve the two sets of inverse kinematic solutions of the mechanism and verification，and the particle swarm optimization algorithm is used to study and establish the positive solution model of the mechanism under the R phase and verify. Finally，software to solve the mechanism's reachable workspace under the R phase and the translational workspace under the U phase are solved using SolidWorks combing with Matlab. The research results provide theoretical support for the further optimization and practical application of the mechanism.